Critical review of the gain factor of 16 for calculation of the Raman threshold in fibers - Engelbrecht, Rainer (Conference on Lasers and Electrooptics (CLEO:2015), 2015)
Analytic approximations yielding the well-known gain factor of 16 in formulas for SRS threshold in fibers are compared to rigorous simulations. This factor is shown to be larger for short and modern fibers, as used for high-power lasers.
lhft_intern.bib::engelbrecht15b